A study on the performance of passively heated solar houses - Neba-Fabs, N. E. (Cranfield University, 1990)
In this paper , analytical techniques are developed for evaluating the performance of passively heated buildings. As most buildings use conservatories to enhance their performance , the direct gain types having attached conservatories are considered in detail. The complexity of the problem is minimized by ensuring all equations are developed from first principles. Auxilliary energy predictions for space heating by the method is in close agreement with monitored data for three occupied houses in Milton Keynes in England.